2018
DOI: 10.1007/s00401-018-1868-1
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease pathology propagation by exosomes containing toxic amyloid-beta oligomers

Abstract: The gradual deterioration of cognitive functions in Alzheimer’s disease is paralleled by a hierarchical progression of amyloid-beta and tau brain pathology. Recent findings indicate that toxic oligomers of amyloid-beta may cause propagation of pathology in a prion-like manner, although the underlying mechanisms are incompletely understood. Here we show that small extracellular vesicles, exosomes, from Alzheimer patients’ brains contain increased levels of amyloid-beta oligomers and can act as vehicles for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
297
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(304 citation statements)
references
References 60 publications
7
297
0
Order By: Relevance
“…Of note, these flotillin-positive EV-mediated effects have been shown to be prevented via Aβ antibody treatment, highlighting the essential role of Aβ in the EV-induced neurotoxicity [37]. Furthermore, another study has demonstrated that flotillin-1-positive exosomes isolated from postmortem brain sections of AD patients were highly enriched in toxic Aβ oligomers compared with healthy controls, which could be transferred into recipient's cultured neurons [38]. Disruption of the production, release, or uptake of these exosomes was shown to attenuate the spreading of Aβ oligomers and Aβ-induced neurotoxicity [38].…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, these flotillin-positive EV-mediated effects have been shown to be prevented via Aβ antibody treatment, highlighting the essential role of Aβ in the EV-induced neurotoxicity [37]. Furthermore, another study has demonstrated that flotillin-1-positive exosomes isolated from postmortem brain sections of AD patients were highly enriched in toxic Aβ oligomers compared with healthy controls, which could be transferred into recipient's cultured neurons [38]. Disruption of the production, release, or uptake of these exosomes was shown to attenuate the spreading of Aβ oligomers and Aβ-induced neurotoxicity [38].…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…Furthermore, another study has demonstrated that flotillin-1-positive exosomes isolated from postmortem brain sections of AD patients were highly enriched in toxic Aβ oligomers compared with healthy controls, which could be transferred into recipient's cultured neurons [38]. Disruption of the production, release, or uptake of these exosomes was shown to attenuate the spreading of Aβ oligomers and Aβ-induced neurotoxicity [38]. Furthermore, a neuropathological study in brain tissues from AD patients has also reported that flotillins are also present in granulovacuolar degeneration (GVD) bodies [39], which are basophilic perinuclear vacuoles accumulating in neurons of AD patients [40].…”
Section: Evidence From Human Studiesmentioning
confidence: 99%
“…in AD, it was found that a portion of Aβ was secreted by exosomes, and that exosome specific proteins were found enriched in amyloid plaques of AD patients . Further studies have identified that brain‐derived exosomes from AD patients contained increased levels of Aβ aggregates and that blocking the secretion or uptake of these exosomes in vitro could reduce the spread of these aggregates and their associated cytotoxicity . Microglia, the primary phagocytes in the brain have been shown to be positively correlated with tau pathology in AD.…”
Section: Role Of Exosomesmentioning
confidence: 99%
“…The abnormal accumulation and aggregation of disease-specific proteins could form intracellular inclusions or extracellular aggregates [68]. Amyloid beta and tau deposition in the brain has been identified as a toxic event by which exosome mediates to impair synaptic structure and function in Alzheimer's disease [69], while the progressive accumulation of α-synuclein in the brain through exosomes has been linked to Parkinson's disease [50,70]. Recent evidence has also implicated exosomes in aging processes [71].…”
Section: Exosomes In Neurodegenerationmentioning
confidence: 99%